Women and leadership in the news media 2023: evidence from 12 markets - Adams, K; Ross Arguedas, A; Mukherjee, M; Nielsen, RK (Reuters Institute for the Study of Journalism, 2023)
In this Reuters Institute factsheet, we analyse the gender breakdown of top editors in a strategic sample of 240 major online and offline news outlets in 12 different markets across five continents. Building off work started in 2020, we find in 2023 that only 22% of the 180 top editors across the 240 brands covered are women. In 2022, this percentage was 21% across the 240 brands covered. In 11 out of 12 markets, the majority of top editors are men; no market in our sample has a majority of women top editors this year. We find weak positive correlations between the percentage of women working in journalism with the percentage of women in top editorial positions as well as between gender inequality in society and the percentage of women top editors. Findings indicate no clear overall trend towards greater gender equality in top editorial positions.